María, alumna de la paz. (2016)
Abstract The Christian people have always seen concentrated in Mary the best human virtues. It is no wonder that peace has also been related to her. Eucharistic liturgy classifies her as student of peace. After a series of anthropological considerations that may apply to her as a symbol of peace, the article (with appropriate references to Mary) analyzes the Christological implications that break any hint of violence that can appeal to the gospel. Also a littleknown text by St. Thomas Aquinas concerning peace is analyzed. To finish by appealing to forgiveness as one of the best roads that lead to peace and allow to live in liberty.